Mastering Your fellowship: Part 4, 2023 - Mergan Naidoo; Klaus von Pressentin; Tasleem Ras; Gert Marincowitz (South African Family Practice)
The ‘Mastering your Fellowship’ series provides examples of the question format encountered in the written and clinical examinations, Part A of the Fellowship of the College of Family Physicians of South Africa (FCFP [SA]) examination. The series is aimed at helping family medicine registrars prepare for this examination.